2023
DOI: 10.3390/ma16083276
|View full text |Cite
|
Sign up to set email alerts
|

Glass-Ceramic Coating on Silver Electrode Surface via 3D Printing

Abstract: Silver electrodes are commonly used as a conductive layer for electromagnetic devices. It has the advantages of good conductivity, easy processing, and good bonding with a ceramic matrix. However, the low melting point (961 °C) results in a decrease in electrical conductivity and migration of silver ions under an electric field when it works at high temperatures. Using a dense coating layer on the silver surface is a feasible way to effectively prevent the performance fluctuation or failure of the electrodes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It can be seen from Table 4 that we can increase the bulk density of the ce ramics by adding a little amount of TiO2 to Cr/Mn-doped Al2O3 ceramics. The bulk density of the Al2O3 ceramics with 1 wt.% TiO2 is highest, reaching 3.810 g/cm 3 . After that, the bulk density of the Al2O3 ceramics decreases with the increase in the content of TiO2.…”
Section: Bulk Density and Micromorphologymentioning
confidence: 96%
See 1 more Smart Citation
“…It can be seen from Table 4 that we can increase the bulk density of the ce ramics by adding a little amount of TiO2 to Cr/Mn-doped Al2O3 ceramics. The bulk density of the Al2O3 ceramics with 1 wt.% TiO2 is highest, reaching 3.810 g/cm 3 . After that, the bulk density of the Al2O3 ceramics decreases with the increase in the content of TiO2.…”
Section: Bulk Density and Micromorphologymentioning
confidence: 96%
“…Studies have shown that as a solid insulator, the voltage holdoff capacity of Al 2 O 3 ceramics in a vacuum is often lower than vacuum gaps of the same size. The surface of the insulator is the weakest point in vacuum-insulation systems because its bulk voltage holdoff capacity is generally greater than the vacuum gap of the same size [ 3 , 4 ]. Surface flashover occurs in many vacuum electronic devices when the applied voltage exceeds a certain value, resulting in the failure of or damage to the device [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%